Determination of the factors that influence customer satisfaction of banking services in the city of Guayaquil - Abarca, Erick; Acosta, Andrea; Bajaña, Yanina (Revista Universidad de Guayaquil, 2020)
The objective of this research is to examine the quality with which services are provided in the financial sector of the city of Guayaquil, for this purpose an analysis of the factors that affect customer satisfaction with banking services is proposed, in this way it is intended Recognize the most relevant constructs while trying to know a measurement tool. To begin with, a thorough literature review related to basic theories such as SERVQUAL, SERVPERF and BankServ is carried out in order to build a tool that helps to measure customer satisfaction, this is done through descriptive statistics and correlational of the collected data. The research allows us to conclude that there are four factors that positively influence the satisfaction of clients of Guayaquil banking services: quality of service, environment, accessibility and the financial factor.